ROLE OF SHADOW ECONOMICS IN FORMATION OF RURAL POPULATION’S INCOME - Дворник, І. В. (Scientific Progress & Innovations, 2015)
This article explores the basic manifestations of shadow economics in the process of formation of rural population’s income. The main sources of unreported income are: wages «in an envelope», providing services, sale of agricultural products on a market. Schemes of use of «white», «grey» and «black» wages as well as principle model of underground economy are presented. The system of measures from the side of the state as for supporting rural population and control of leading shadow activity by employers are offered.